MANAJEMEN PEMBELAJARAN MATEMATIKA MENGGUNAKAN ALAT PERAGA BLOK PECAHAN, LINGKARAN DAN KARTU PECAHAN - Sulistyorini Sulistyorini (Manajer Pendididikan, 2017)
This study examines the learning management menggumakan Viewer tool Block Denomination circle and cards learning material fractions fractions in Class III State Elementary School 08 Kabawetan two semester academic year 2013/2014. The subject of this research is a Class III student as much as 21 0rang. Stages of learning is done to raise the student learning outcomes using the media circle, then with the provision of individual tasks seta followed by the task group, where each member of the group can reflect results of individual assignments friend group. Then each group diebri opportunity to mepresentasikan the circle model, and may terminate by giving affirmation and reward to the group accompanied by the provision of gifts, in order to motivate students to study harder mathematics and mathematics learning not be scary